Hybrid raman-erbium random fiber laser with symmetrical combined pumping of 1455 nm and 1497 nm wavelengths - Zainol Abidin, Nadiah Husseini; Abu Bakar, Muhammad Hafiz; Mahdi, Mohd Adzir (Journal of Multidisciplinary Engineering Science and Technology (JMEST), 2019)
This paper demonstrates an 80 km random fiber laser with and without the integration erbium-doped fiber (EDF). The scheme employs combined pumping wavelength scheme of 1455 nm and 1497 nm where variation in power of both pumps are performed and its corresponding optical spectral output is analyzed. Two broad Raman peaks at 1567 nm and 1597 nm is exhibited in the scheme without EDF due to the superpositioning of Raman spectral profiles. With the integration of EDF, the net gain profile is higher in the L-band as the 1497 nm pump emission is at an advantage from gain tilt effect.